Sequence stratigraphic distribution of coal-bearing rocks from the Mesaverde Group in the easternmost Atlantic Rim of the Washakie Basin, Wyoming - Dereume, Jeffrey Michael, author; Egenhoff, Sven O., advisor; Harry, Dennis L., committee member; von Fischer, Joseph C., committee member (Colorado State University. Libraries, 2010)
Coals occur in various levels of the siliciclastic Campanian upper Mesaverde Group in the Atlantic Rim area, Washakie Basin, south central Wyoming. This unit consists of continental, delta, and offshore facies showing several orders of internal cyclic architecture. At least five large-scale cycles form the upper part of the Mesaverde Group, internally arranged in stacks of up to five medium-scale cycles that are in turn subdivided into a maximum of five small-scale cycles. These cycles reflect million-year to Milankovitch-type sea-level fluctuations causing trans- and regression of varying magnitude, within an overall transgressive regime. Coals developed preferentially in paralic and lower coastal plain environments in the Atlantic Rim in relative proximity to a nearby delta. The position closest to the shoreline was occupied by coal-rich mudstones reflecting siliciclastic input from the delta and the sea during floods. Both coals and coal-rich siliciclastic mudstones occur during all stages of a sea-level curve. While previous models suggested a preferential accumulation of coals during early transgressions, a peak in coal frequency characterizes early regressive sediments within the Mesaverde Group in the Atlantic Rim. This is believed to be the result of a heightened water table during early regressions promoting anoxic swamp and marsh environments, and frequent flooding of floodplains forming an ideal setting for accumulation of organic matter. The lateral continuity of Mesaverde coals is also positively influenced by development within paralic settings. Many of the most correlative coal seams in the Atlantic Rim occur within close stratigraphic proximity and/or lateral to marine deposits. Integrating a sequence stratigraphic framework into the upper Mesaverde Group significantly enhances prediction patterns of coaly rocks by constraining their stratigraphic and lateral distributions. Clay- and silt-bearing organic-rich mudstones mark the transition from continental to marine facies, while pure coals only occur at a distance from the shoreline. The overall transgressive nature of the upper part of the Mesaverde Group reveals a highly diachronous facies distribution within the Washakie Basin. A significantly thicker coal-bearing interval characterizes the southern part, while successions further north show abundant mudstones, representing an overall earlier transition to marine conditions.
Keywords: coal; correlation; Mesaverde; sedimentology; sequence; stratigraphy